High level expression and purification of HhaI methyltransferase. - Wu, J C (1988)
A cloning system for the DNA-(cytosine-5)-methyltransferase MHhaI and high level expression of the enzyme are described. A parent plasmid was constructed from fragments of the MHhaI gene and synthetic oligonucleotides. The construct permits introduction of various restriction sites for cloning at precise positions near the initiation codon, and beyond the termination codon. The entire MHhaI coding sequence was introduced as a 1042 b.p. NdeI-XbaI fragment into the vector pAR3040 which contains the T7 RNA polymerase promoter. The resultant plasmid pTNX3 (MHhaI-pAR3040) was introduced into McrB- E. coli strains HB101 and GM2929, and expression of MHhaI was induced by infection with the lambda phage CE6 carrying the T7 RNA polymerase gene. In induced cells, catalytically active MHhaI was produced at a level that corresponds to about 8% of the total soluble protein; an insoluble form of the protein was also formed, but could be readily removed. The expressed soluble enzyme from HB101/pTNX3 was purified to apparent homogeneity in about 50% yield by a two-step chromatographic procedure involving DEAE-cellulose and Heparin-Sepharose; a one liter culture gave about 2.5 mg of pure enzyme. The molecular weight and kinetic properties of the expressed protein are identical to those reported for the authentic MHhaI, and its amino terminal sequence agrees with that predicted from the DNA sequence.